Socio-educational function of a punishment and conceptions of human nature (on the example of Michael Baurmann conception) (Archives of Criminology, 2009)
In the present debate on theory of positive general prevention more emphasis is put on empirical than normative issues. It is understandable since the number of empirical studies, proving the theses of moral-educational role of the punishment, carried out so far is low and the results are inconclusive and preliminary. This justifies the question if these theories have any grounds in social reality. It is even suggested that the theories are lawyers’ ideas and their greatest asset is the difficulty of obtaining an empirical proof. Because of this, one may refer to them without a fear that the claims will be rejected in empirical research (disregarding purely normative theories, that is). What is a characteristic feature of various version of positive general prevention is that it is meant to be achieved not by fear of punishment but other mechanisms which do not emphasise the element of constraint and real affliction of state-imposed punishment. It is most of all about emphasising persuasive, educational, socialising and symbolic character of criminal law impact as well as about creating a habit. In some theories, state-imposed punishment plays a role of an argument in shaping rationally motivated convictions which should favour voluntary obedience of criminal law norms. Since state-imposed punishment becomes a motivating measure which can be combined with autonomy and dignity of an individual, ethical reservations concerning it use are eliminated to a great extent. Because of this masking of the real character of stateimposed punishment, this is the point where the risk of its broader use appears. Therefore the primary task is to restate the theory of positive prevention into a general empirical theory whose claims can be verified. Previous studies have shown that these theories are available for empirical research, which belies the widespread belief that they can not be subjected to empirical verification. There is no doubt that the rearrangement of the thesis of general positive prevention and making terminology more precise would help in building an empirical theory. The biggest challenge is to develop a theoretical model of human behaviour which could support the theory of general positive prevention. The need to provide such a theoretical model of human behaviour was shown by German sociologist, Michael Baurmann, and it was him who undertook this task. Importantly, not only has he developed such a model, but he applied it directly to reformulate selected varieties of positive general prevention in an empirical theory. On an example of two models designed for different versions of positive general prevention, Baurmann showed not only how to organize the varieties of moral and educational theory of punishment, but also how to describe them in the language of empirical research. General prevention understood as general deterrence is based on a model of rational choice in the sense of homo economicus.